Caracterização de alelos de gluteninas de alto peso molecular, influência sobre a qualidade de uso final de trigo no Brasil e análise de marcadores moleculares - Vancini, Camila (2018)
The objective of this work was to characterize the high molecular weight glutenin subunits (HMW-GS) and to analyze their relation with parameters of wheat technological quality in a collection of wheat genotypes with importance in the introgression of characteristics of interest by breeding programs in Brazil. A total of 274 accessions of wheats were evaluated by SDSPAGE, and for 219 accessions with homogeneity for HMW-GS 53 profiles and 21 alleles were found. The most frequent combination was 2 */7+9/5+10 (11.9%). Based on the protein profile of HMW-GS and the identification of 7oe allele overexpression and 1BL.1RS translocation with DNA molecular markers, the Glu-1 score was calculated and the correlations with wheat technological quality parameters were analyzed. The main effects of the Glu-1 and 1BL.1RS loci were estimated using the maximum likelihood-restricted algorithm (REML). The Glu-1 score showed significant correlations with the QTT: sodium dodecylsulfate microssedimentation (MSSDS);alveography with gluten strength (W), tenacity (P), extensibility (L) and elasticity index (Ie) and pharynography, with the parameter stability (ST) with values of correlation coefficient (r) varying from 0.27 to 0.51. Alleles 1, 7oe+8 and 5+10, located at the Glu-A1, Glu-B1 and GluD1 loci, respectively, had higher values for W, Ie and ST. The results indicated that an adjustment to the Glu-A1 locus alleles score for Brazil conditions of cultivation is required as well as the use of molecular markers for the identification of the 7oe+8 combination. SNP (single nucleotide polymorphism) molecular markers were used to analyze 467 accessions of wheat by the KASP method for alleles of the Glu-A1 and Glu-D1 loci and for translocation 1BL.1RS. The SDS-PAGE analysis of 270 of the accessions allowed the comparison of the results with the DNA analyzes. For the Glu-A1 locus marker there was 91.8% agreement with the protein profile of HMW-GS and for locus Glu-D1, 98.8%. For the Glu-B1 locus marker of superexpression 7oe and 22 (10%) were identified with this allele. The presence of 1BL.1RS translocation was identified in 83 (18%) of the 467 accessions of wheat. The results indicated the efficiency in the use of molecular markers for the Glu-1 loci.